Prevalence and severity of orofacial pain in pregnant women - Rosell, Fernanda Lopez; Valsecki JÚnior, Aylton; Tagliaferro, Elaine Pereira Da Silva; Silva, Silvio Rocha Corrêa da [UNESP] (Faculdade São Leopoldo Mandic, 2014)
OBJECTIVE:To evaluate the prevalence and severity of oral pain in pregnant women.METHODS:A cross-sectional study was conducted on a sample of pregnant women who were receiving dental care at a Dental School. A structured questionnaire about self-perception of oral conditions and the presence and severity of orofacial pain in the mouth or teeth in the last 6 months was applied.RESULTS:80 pregnant women participated in the study and, of these, 58.8% reported having a problem with their teeth, 31.3% periodontal problems, 61.3% bad taste in mouth and 62.5% bad breath. Only 22.5% of pregnant women did not exhibit any form of oral pain. The most frequently reported pains were: pain with hot/cold liquids or sweets (56.2%) and spontaneous toothache (38.8%). With regard to severity, mild and moderate pain were the most frequently reported, but there was a group of 23.8% of pregnant women with severe or very severe pain caused by hot or cold liquids and 18.8% in the same condition in relation to spontaneous pain.CONCLUSION:The results of this study showed that, despite the high prevalence of pain detected in the pregnant women, severity was low and referred to specific situations.

OBJETIVO: Avaliar a prevalência e a severidade da dor orofacial em gestantes. MÉTODOS: O estudo transversal foi realizado em uma amostra de gestantes em atendimento odontológico em uma faculdade de odontologia. Foi aplicado questionário estruturado com perguntas sobre a auto percepção das condições bucais e a presença e a severidade da dor orofacial sentida na boca ou dentes nos últimos 6 meses. RESULTADOS: Participaram do estudo 80 gestantes e, destas, 58,8% afirmaram ter algum problema nos dentes, 31,3% problema na gengiva, 61,3% gosto ruim na boca e 62,5% mau hálito. Apenas 22,5% não apresentaram nenhum tipo de dor orofacial. As dores mais relatadas foram: dor com líquidos quentes, frios ou doces (56,2%) e dor de dente espontânea (38,8%). Quanto à severidade, as dores de intensidade leve e moderada foram as mais frequentes, mas havia um grupo de 23,8% das gestantes com dores intensas ou muito intensas provocadas por líquidos frios ou quentes e 18,8% na mesma condição em relação à dor espontânea. CONCLUSÃO: Os resultados do estudo mostraram que, apesar da alta prevalência de dor orofacial encontrada, a severidade foi baixa e relacionada a algumas situações específicas.
Prevalência e severidade da dor orofacial em gestantes
Keywords: Saúde bucal; Dor; Gestantes; Oral health; Pain; Pregnant women